EXTH-34. COMBINED USE OF THE PAN-IDH MUTANT INHIBITOR AG-881 WITH RADIATION THERAPY SHOWS ADDED BENEFIT IN AN ORTHOTOPIC IDH1 MUTANT GLIOMA MODEL IN VIVO. Issue 11 (6th November 2017) - Nicolay, Brandon; Narayanaswamy, Rohini; Amatangelo, Michael D; Aguado, Elia; Nagaraja, Raj; Murtie, Josh; Liu, Guowen; Ishii, Yuko
Abstract: Mutations in isocitrate dehydrogenase (IDH) 1 or 2 occur in >70% of diffuse low-grade gliomas (LGG). IDH1/2 mutations result in accumulation of the oncometabolite 2-hydroxyglutarate (2-HG), which facilitates tumorigenesis through DNA hypermethylation, increased repressive histone methylation, and inhibition of differentiation processes. Prior studies with an early tool compound, AGI-5198, which is active against mutant IDH1 (mIDH1) but not mutant IDH2 (mIDH2), suggest that inhibition of mIDH1 proteins can repress growth of mIDH1-driven gliomas. Furthermore, recent in vitro studies using AGI-5198 in mIDH1 glioma models have suggested that inhibition of mIDH1 proteins may be antagonistic to the LGG standard of care treatment of radiation + temozolomide (DNA alkylating agent). AG-881, a novel, potent, clinical stage inhibitor of both the mIDH1 and mIDH2 proteins was tested in subcutaneous and orthotopic mouse xenograft models of a human mIDH1-R132H grade III oligodendroglioma alone or in combination with either radiation or temozolomide. AG-881 treatment was well tolerated and the pharmacokinetic properties of AG-881 allowed for oral administration, which resulted in >98% inhibition of 2-HG production by mIDH1 tumors in the brain. We demonstrated that mIDH1 inhibition with AG-881 impedes glioma growth in vivo. The combination of AG-881 + radiation therapy produced a significantly greater effect on tumor growth inhibition when compared with each single-modality treatment alone. This combined-modality treatment benefit was observed both in mice given concomitant AG-881 + radiation therapy and mice treated sequentially with radiation therapy followed by AG-881 treatment. No antagonism with temozolomide or radiation therapy was observed in these in vivo models. Studies in preclinical models to further understand the distinct differences between results with AG-881 and AGI-5198 are ongoing. Taken together, these data support the further investigation of mIDH1 inhibition in combination with radiation in the clinic.